Efektivitas Layanan Bimbingan Kelompok dengan Teknik Brainstorming untuk Meningkatkan Kepercayaan Diri pada Siswa Kelas X SMA di Kota Kisaran - Yuni Dwi Kartika; Alfin Siregar (Jayapangus Press, 2023)
The purpose of this study was to investigate the extent to which grade X students at SMAS Taman Kisaran, who showed a lack of confidence, behaved calmly during teaching and learning activities, and refrained from asking questions about concepts they did not understand through the use of group tutoring services that used brainstorming strategies. This study used a quantitative approach with one group pretest-posttest design experiment design. This research method uses a confidence questionnaire. In this study, we used SPSS 25 For Windows to perform a Paired Sample T-Test analysis of the data. The results showed that while the average pre-treatment score on the self-confidence survey was 70.30 (still in the middle range), the average post-treatment score was 95.60 (in the high range). The normality test used is Shapiro-Wilk. The results of the statistical test with the calculation of Paired Samples T-test showed tcount = -7.698 ≥ ttable -2.306 so that Ho was rejected and Ha was accepted. Thus group tutoring services using brainstorming techniques are quite effective can increase students' confidence. These findings are further supported by observations made by the researchers and interviews conducted with participants, both of which show that students have the ability to honestly express their sentiments, to solve problems, to control their emotions, and to make decisions quickly and appropriately.